Cyborgi – literacko-filmowe figury dyskursu interaktywnego - Gajewska, Grażyna (Przestrzenie Teorii, 2019)
Gajewska Grażyna, Cyborgi – literacko-filmowe figury dyskursu interaktywnego [Cyborgs – Literary and Film Figures of Interactive Discourse]. „Przestrzenie Teorii” 32. Poznań 2019, Adam Mickiewicz University Press, pp. 179–196. ISSN 1644-6763. DOI 10.14746/pt.2019.32.9. The author analyzes the figure of the cyborg in science fiction literature and film. The text begins by showing this kind of literary work in the theoretical field and presents it as an interactive discourse. The author describes the scientific roots of constructing a human-technical hybrid, emphasizing the ideological and political context of this research. In this approach, the cyborg appears as a participant in and also a hostage of the Cold War. Next, the author finds literary and film creations of cyborgs inspired by this political and military heritage. The article also presents alternative images of cyborgs co-creating a feminist and postcolonial discourse. They were also included in specific policies and strategies aimed at deconstructing concepts such as sex and gender, sexuality, race, nation, social class. The main thesis of the article is that as fictitious and real entities, cyborgs are prone to ideologization and burdened with the obligation to politicize. Therefore, when studying cyborgs in literature, film and comics, we must ask what ideologies and politicians they serve.